Progresivitas Pemikiran Lora Thohir dalam Membangung Kemajuan Pendidikan Pesantren Mambaul Ulum Bata-Bata - Sarim Karimullah, Suud (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2021)
This study discusses the progressive thinking put forward by a young pesantren kiai from Madura, namely Lora Thohir. Lora Thohir's progressive thinking brings a new color to pesantren education in general and in particular to the progress of education at Mambaul Ulum Bata-Bata Islamic Boarding School. In this study, it is very interesting to study as an effort to preserve the ideas of various figures in Islamic boarding schools who have contributed to the progress of Islamic education in Indonesia, including the results of Lora Thohir's thoughts on the progress of Islamic boarding school education. Then, library research is the type in this research with a descriptive-explorative qualitative approach. In other words, this research is a character study with data analysis using content analysis techniques through inductive patterns. Furthermore, the results of this study indicate that the existence of Lora Thohir has significantly positive impacts on the progress of education at the Mambaul Ulum Bata-Bata Islamic Boarding School. With progressive thinking, he is able to provide a new color for the development of pesantren education in the midst of modernization life with technological advances without having to leave the traditional values ​​of pesantren. The influence of Lora Thohir's progressive thinking in the field of education in general demands the formation of a complete human being or a perfect human being in the students. Meanwhile, in the implementation of Lora Thohir's progressive thinking in Mambaul Ulum Bata-Bata Islamic Boarding School Education, it is proven by the existence of several programs to develop knowledge among the students in the pesantren.